Biocontrol ability of killer yeasts (Saccharomyces cerevisiae) isolated from wine against Colletotrichum gloeosporioides on grape. (6th November 2017) - Liu, Zongling; Du, Shuang; Ren, Yi; Liu, Yanlin
Abstract : A total of 216 killer yeasts Saccharomyces cerevisiae, isolated from wine, were evaluated in controlling Colletotrichum gloeosporioides, a pre‐harvest anthracnose agent of grape. Three of these yeast isolates were tested positive for antagonizing C. gloeosporioides and were further evaluated for their mechanisms as biological control agents (BCAs): production of antifungal compounds, production of hydrolytic enzymes, inhibition of C. gloeosporioides conidia germination, colonization on grape berry, and efficiency in controlling anthracnose of grape. The results showed that all three S. cerevisiae isolates produced antifungal compounds, inhibited C. gloeosporioides conidia germination and produced β‐1, 3‐glucanase and chitinase. All isolates colonized grape berry in large quantities and controlled C. gloeosporioides when artificially inoculated on grape berry. Among the three isolates, application of isolate GA8 resulted in 69.7% of disease reductions for C. gloeosporioides on grape berry. The antagonistic isolates of S. cerevisiae could represent important BCAs of anthracnose of grape caused by C. gloeosporioides that are responsible for economic losses in viticulture.